2022
DOI: 10.3390/bios12070438
|View full text |Cite
|
Sign up to set email alerts
|

Evanescent Wave Optical-Fiber Aptasensor for Rapid Detection of Zearalenone in Corn with Unprecedented Sensitivity

Abstract: Zearalenone (ZEN) is a common mycotoxin pollutant found in agricultural products. Aptamers are attractive recognition biomolecules for the development of mycotoxin biosensors. Even though numerous aptasensors have been reported for the detection of ZEN in recent years, many of them suffer from problems including low sensitivity, low specificity, tedious experimental steps, high-cost, and difficulty of automation. We report here the first evanescent wave optical-fiber aptasensor for the detection of ZEN with un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…The most popularly used route consists of several steps: (1) oxidation to form hydroxyl groups, (2) silanization to convert the hydroxyl groups into an amino group, (3) the transformation of the amino to an aldehyde group by amine aldehyde condensation reaction, (4) covalently coupling the amino-modified nucleic acid probes, and (5) reduction of the less-stable imine bond into a C-N single bond and the unreacted aldehyde groups into hydroxyl groups by NaBH 4 reduction [ 50 ]. Many works use a similar approach to immobilize amino aptamers on the fiber surface with slight differences [ 51 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. For examples, glycine [ 60 , 79 ] and NaCNBH 3 [ 60 , 80 ] were used to deplete the remaining aldehyde sites after the coupling of aptamers.…”
Section: Optical Fiber Interfacial Modification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most popularly used route consists of several steps: (1) oxidation to form hydroxyl groups, (2) silanization to convert the hydroxyl groups into an amino group, (3) the transformation of the amino to an aldehyde group by amine aldehyde condensation reaction, (4) covalently coupling the amino-modified nucleic acid probes, and (5) reduction of the less-stable imine bond into a C-N single bond and the unreacted aldehyde groups into hydroxyl groups by NaBH 4 reduction [ 50 ]. Many works use a similar approach to immobilize amino aptamers on the fiber surface with slight differences [ 51 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. For examples, glycine [ 60 , 79 ] and NaCNBH 3 [ 60 , 80 ] were used to deplete the remaining aldehyde sites after the coupling of aptamers.…”
Section: Optical Fiber Interfacial Modification Methodsmentioning
confidence: 99%
“…Different from the target or cDNA-immobilized strategies, the NADL-FOEW sensor enables in situ target enrichment, purification, and sensing on the same surface simultaneously, therefore dramatically improving the LOD down to the unprecedented femtomolar ranges. So far, we have demonstrated the ultrasensitive and specific detection of kanamycin [ 50 ], sulfadimethoxine [ 50 ], di-(2-ethylhexyl) phthalate [ 50 ], zearalenone [ 77 ], sulfonamides [ 71 ], and alternariol [ 72 ] in diverse matrices including environmental water, fresh milk, wine, wheat, and corn extracts. Both the detection sensitivity and the dynamic range all meet the practical applications.…”
Section: Sensing Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic sensing mechanism of the EF-based hydrogen sensor depends on the interaction of evanescent field at the interface of the optical core fiber and sensing layer. These evanescent field decays exponentially corresponding to increasing the distance from the exposed core, and the attenuation coefficient depends on the refractive index of the fiber cladding [63]. These techniques were exploited to increase the intensity of the evanescent field at interface and improve the light-matter interaction to the hydrogen.…”
Section: Evanescent Field (Ef) Based Hydrogen Sensor (Side Polished/t...mentioning
confidence: 99%
“…The innate stability of synthetic receptors makes them well-suited for sensor platforms where the limited shelfstability of antibodies could be problematic. Zhao et al (2022) reported on a portable evanescent wave opticalfibre sensor that employed a ZEN specific aptamer as the recognition layer. The sensor consisted of the optical system (laser, optical fibre coupler, filter, photodiode, and signal amplifier) and a fluidic system (peristaltic pump, tubes, reaction chamber).…”
Section: Assays With Antibody Analoguesmentioning
confidence: 99%